Subject and truth a critical evaluation of Alain Badiou s mathematical ontology - Sandhya V P (Department of Philosophy, University of Calicut, 2025)
This study pursues a twofold objective. Firstly, it undertakes an in-depth examination of Alain Badiou’s philosophical system, focusing especially on his linking of set theory to ontology, concept of the ‘event’, concept of the formation of the ‘subject’, and his views on the conditions that render ‘truth’ possible. Secondly, it provides a general critical evaluation of Badiou’s philosophical framework, assessing its implications and limitations. This critical evaluation helps us to develop a critical perspective on some fundamental tensions in linking set theory to ontology and, more importantly, provides us with a platform to have a critical view on how Badiou’s system involves the elements of what can be called a correlative subjectivism which problematize its initial purpose
Keywords: Mathematical ontology; Set Theory; Subject; Event; Truth